Using Arts-Based Methods and Reflection to Support Postgraduate International Students’ Wellbeing and Employability through Challenging Times - Watson, Marthy; Barton, Georgina (Journal of International Students, 2020)
This paper reports on an arts-based research study that aimed to support international students to reflect on their studies and personal working lives during the COVID-19 global pandemic. The authors implemented a reflective process involving mindfulness and body mapping to support international students in expressing their experiences and feelings during this time. Results show that the international students gained a deeper understanding of what they experienced personally and how these experiences were both different and similar to their peers. The process enabled students to acknowledge and accept challenges faced as well as provided a safe avenue to do so. They reported the powerful nature of the arts-based methods in helping them think positively about their studies and future working lives.